(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
The article deals with the investigation of the stylistic features of the English headlines and their problems in their teaching to intermediate students play an important role in studying English as a second language. The newspaper is one of the oldest mass media resources and it is highly demanded nowadays, for example: they are printed and published almost in every language all over the world. It shows that despite of our fast changing world, newspapers till now play a very significant role. It can be assumed that factors which make newspaper important are: mobility, availability, periodicity, officiality and universality that is everyone can find there something interesting and useful for oneself. The study of the English headlines and their peculiarities in English holds significant linguistic, pedagogical, and cognitive relevance.